ERMENİ MESELESİ BAĞLAMINDA TÜRK-FRANSIZ İLİŞKİLERİNİN DÜNÜ VE BUGÜNÜ / TURKISH-FRENCH RELATIONS IN THE CONTEXT OF THE ARMENIAN QUESTION: PAST AND PRESENT - Karacakaya, Recep (Journal of History Culture and Art Research, 2012)
ERMENİ MESELESİ BAĞLAMINDA TÜRK-FRANSIZ İLİŞKİLERİNİN DÜNÜ VE BUGÜNÜ Özet Fransa, tarihi ve dini bağlar dolayısıyla Ermenilerle çok eski tarihlerden beri ilgilenmiş, Ermenileri kendi çıkarları için kullanmaktan çekinmemiştir. Fransız siyasetçiler daha 1890’lı yıllardan itibaren Ermenileri iç siyaset aracı olarak kullanmışlar ve aynı geleneği 2000’li yıllarda da sürdürmekten vazgeçmemişlerdir. Ermeniler de Fransa’ya dayanarak önce Osmanlı Devleti’nden, sonra ise Türkiye Cumhuriyeti Devleti’nden bazı politik kazanımlar elde etmeye çalışmışlar ve son yıllarda da büyük devletlerin baskısıyla soykırım iddialarını Türkiye’ye kabul ettirmeye çalışmışlardır. TURKISH-FRENCH RELATIONS IN THE CONTEXT OF THE ARMENIAN QUESTION: PAST AND PRESENT Abstract France has dealt with the Armenians since the ancient tımes due to historical and religious ties, so that she has not hesitated to use them for their own interest. French politicians have used Armenians as an instrument of domestic politics since the 1890s, and continue to practice the same tradition even today. With the encouragement and help of France, Armenians first tried to achieve some concessions from the Ottoman Empire and later on from the new Turkish Republic. Even in recent years, Armenians have been trying to have Turkey accept the so-called Armenian genocide with the help of some leading powers’ pressure. RELATIONS TURCO-FRANÇAISES DANS LE CADRE DE LA QUESTION ARMÊNİENNE: PASSÉ ET PRÉSENT Résumé En raison de liens historiques et religieux, la France s’est intéressée aux Arméniens depuis très longtemps et n’a pas hésité à les utiliser pour ses propres intérêts. Les politiciens français ont déjà utilisé les Arméniens à partir de 1890 comme un instrument de politique intérieure et ont poursuivi cette tradition à partir des années de 2000. Quant aux Arméniens, en s’appuyant sur la France, ils ont essayé d’obtenir quelque chose d’abord de l’Empire ottoman et puis de la République Turque et ont voulu faire accepter par la Turquie ces dernières années les revendications de génocide sous la pression des Etats les plus puissants. العلاقات الفرنسية والتركية في سياق المسألة الأرمنية ملخص لقد اهتم فرنسا بالأرمن منذ العصور القديمة بسبب علاقاتها التاريخية والدينية ولم يتردد في استخدام الأرمن لمصالحها الخاصة. وقد استخدم السياسيين الفرنسيين الأرمنَ كأداة من أدوات السياسة الداخلية بدءا من عام 1890 ولم يتركوا مواصلة نفس التقليد في أعوام 2000. كما حاول الأرمن الذين اعتمدوا على فرنسا للحصول على أشياء أولاً من الدولة العثمانية وبعد ذلك من الجمهورية التركية. وفي السنوات الأخيرة قاموا بادعاءات الإبادة الجماعية تحت ضغط من الدول الكبرى.